Determinants of Major Choice and Academic Expectations: Testing a Prediction Model Across Gender - Alfonso, Sonia; Diniz, António M.; Conde, Angeles; García-Señorán, Mar (Frontiers in Psychology, 2022)
With this study, we aim to test the predictive relationships between determinants of major choice (DMC) and academic expectations (AEs) and analyse gender differences, using six items of the Determinants of Major Choice Scale and the Academic Perceptions Questionnaire to assess AEs. A convenience sample of Portuguese (n = 839) and Spanish (n = 1001) first-year students (age-range = 17-23 years), most composed by women (56.9%, n = 1047), was selected from two public universities. The invariance of the multivariate regression model with latent variables of the effect of DMC on AEs, with intrinsic determinants (IDs; e.g., personal characteristics) and mediating agents (MAs; e.g., parents) as AE’s predictors, was tested across gender in LISREL. The invariance test of the multivariate regression model across gender was well fitted to data and revealed an equivalence of slopes between women and men, which allows a unique interpretation of the model’s predictive relationships for both genders. We also found statistically significant predictive relationships of IDs on six factors AEs and MAs on five factors AEs. The results showed, at a theoretical level, relationships with the self-determination theory. At a practical level, they pointed out the importance of IDs and MAs to conceive AEs intervention programs in Higher Education institutions.